Mass Surveillance and the Maqasid al-Shari‘ah: Balancing Security and Human Rights in Contemporary Islamic Discourse - Abdulsatar Shaker Salman (International Journal of Sharia and Law, 2025)
The integration of mass surveillance technologies across Muslim-majority states has introduced complex tensions between state security and Islamic principles of justice, dignity, and personal liberty. While traditional Islamic legal principles emphasize both collective welfare and individual rights, the advent of AI-driven monitoring and predictive surveillance raises ethical concerns within the framework of the Maqasid al-Shari‘ah. This paper aims to examines the intersection between surveillance technologies and the higher objectives of Islamic law (maqasid), particularly how Islamic ethics, legal doctrine, and human dignity can be reconciled with modern demands for state surveillance. Using a doctrinal legal approach, this study evaluates primary Islamic legal sources (Qur’an, Sunnah, and fiqh traditions), contemporary fatwas, and policy frameworks from OIC states. It combines empirical datasets on surveillance practices with theological interpretation of maqasid elements—such as hifz al-nafs (preservation of life), hifz al-din (religion), hifz al-‘aql (intellect), and hifz al-‘ird (dignity). Comparative statistical models also assess correlations between Shariah-based oversight structures and privacy violations. States incorporating Shariah-based principles of maslahah (public interest) and amanah (trust) into surveillance regulation exhibit 30–35% fewer reported privacy infringements. Oversight mechanisms rooted in Islamic values—such as hisbah and shura councils—correlate with lower Surveillance-to-Privacy Ratios (SPR), especially in cases with short data retention and ethical limitations on data use. Statistical modeling confirms that maqasid-centric regulatory approaches yield reductions in public grievances and constitutional challenges to surveillance law. Integrating Maqasid al-Shari‘ah into regulatory surveillance frameworks provides a viable path for Islamic societies to harmonize national security with the sanctity of personal liberty and dignity. Future frameworks must prioritize Islamic values of transparency (as-shaffafiyyah), accountability (al-mas'uliyyah), and social justice (‘adl), thereby ensuring that security measures do not contravene foundational ethical and legal norms.